CFD Simulations of Splash Losses of a Gearbox. (29th August 2012) - Gorla, Carlo; Concli, Franco; Stahl, Karsten; Höhn, Bernd-Robert; Klaus, Michaelis; Schultheiß, Hansjörg; Stemplinger, Johann-Paul
Abstract : Efficiency is becoming a main concern in the design of power transmissions. It is therefore important, especially during the design phase, to have appropriate models to predict the power losses. For this reason, CFD (computational fluid dynamics) simulations were performed in order to understand the influence of geometrical and operating parameters on the losses in power transmissions. The results of the model were validated with experimental results.